Field Efficacy Trials of Different Pesticides against Pieris rapae and Plutella xylostella - Li, Zhao; Wenying, Hong; Yanjun, Wu; Yanxin, Wang; Rui, Chen; Linying, Zhang (Plant Diseases and Pests(植物病虫害研究：英文版), 2014)
Field efficacy trials of different pesticides against Pieris rapae and Plutella xylostella showed that seven pesticides had certain control effects against P.rapae and P. xylostella. 240 g/L Chlorfenapyr SC had the most ideal control effect,with quick effect and long persistence,and the control effects against P. rapae and P. xylostella were 91. 96% and 95. 73% after application for 7 d,respectively. 25% Thiamethoxam WDG 3 000 times dilution had the poorest control effect,and quick effect and persistence were not ideal; the control effects against P. rapae and P. xylostella were 49. 21% and 57. 20% after application for 7 d,respectively. The remaining pesticides had good control effect against both P. rapae and P. xylostella,with certain persistence. Slight injury such as yellowing tender leaves appeared in the area treated with 50% thiocyclam SP,although the injury was reversible,it was still not recommended to use; no other treatments had adverse effects on growth of cabbage.